Application of multi-omic features clustering and pathway enrichment to clarify the impact of vitamin B2 supplementation on broiler caeca microbiome - Mengucci, Carlo; Rampelli, Simone; Picone, Gianfranco; Lucchi, Alex; Litta, Gilberto; Biagi, Elena; Candela, Marco; Manfreda, Gerardo; Brigidi, Patrizia; Capozzi, Francesco; De Cesare, Alessandra (Frontiers in Microbiology, 2023)
The results of omic methodologies are often reported as separate datasets. In this study we applied for the first time multi-omic features clustering and pathway enrichment to clarify the biological impact of vitamin B2 supplementation on broiler caeca microbiome.The caeca contents of broilers fed +50 and +100 mg/kg vitamin B2 were analyzed by shotgun metagenomic and metabolomic. Latent variables extracted from NMR spectra, as well as taxonomic and functional features profiled from metagenomes, were integrated to characterize the effect of vitamin B2 in modulating caeca microbiome. A pathway-based network was obtained by mapping the observed input genes and compounds, highlighting connected strands of metabolic ways through pathway-enrichment analysis.At day 14, the taxonomic, functional and metabolomic features in the caeca of tested broilers showed some degree of separation between control and treated groups, becoming fully clear at 28 days and persisting up to 42 days. In the caeca of birds belonging to the control group Alistipes spp was the signature species, while the signature species in the caeca of broilers fed + 50 and + 100 mg/kg vitamin B2 were Bacteroides fragilis and Lactobacillus crispatus, Lactobacillus reuteri, Ruminococcus torques, Subdoligranum spp, respectively. The pathway enrichment analysis highlighted that the specific biochemical pathways enhanced by the supplementations of vitamin B2 were N-Formyl-Laspartate amidohydrolase, producing Aspartate and Formate; L-Alanine:2-oxoglutarate amino transferase, supporting the conversion of L-Alanine and 2-Oxoglutarate in Pyruvate and L-Glutamate; 1D-myo-inositol 1/4 phosphate phosphohydrolase, converting Inositol 1/4-phosphate and water in myo-Inositol and Orthophosphate. The results of this study demonstrated that the caeca of birds fed +50 and +100 mg/kg were those characterized by taxonomic groups more beneficial to the host and with a higher concentration of myo-inositol, formic acid, amino acids and pyruvate involved in glycolysis and amino acid biosynthesis.In this study we demonstrated how to perform multi-omic features integration to describe the biochemical mechanisms enhanced by the supplementation of different concentrations of vitamin B2 in the poultry diet. The relationship between vitamin B2 supplementation and myo-inositol production was highlighted in our study for the first time.